Installing and configuring Windows Server® 2012 : training guide - Tulloch, Mitch (Microsoft Press WashingtonUS, 2012)
Describes common infrastructure migration scenarios and outlines the steps involved in a typical server-migration process; provides the basic knowledge to deploy servers using the tools and best practices recommended by Microsoft. Shows how to manage Windows servers across environments. Describes how to prepare for the deployment of Windows Server 2012 domain controllers, how to deploy domain controllers using both Server Manager and Windows PowerShell , and how to take advantage of domain-controller vitualisation; configuring Internet Protocol version 6 (IPv6) networking and interoperability between Ipv6 and IPv4. Looks at virtual machines; file services and storage; print and document services; implementing group policy; and configuring Windows Firewall and PIsec.